Co-culture of bone marrow fibroblasts and endothelial cells on modified polycaprolactone substrates for enhanced potentials in bone tissue engineering. - Choong, C; Hutmacher, D; Triffitt, J (2006)
The creation of a vascularized bed makes the survival of seeded cells on 3-dimensional scaffolds much more likely. However, relying purely on random capillary ingrowth into the porous scaffolds from the host may compromise vascularization of a scaffold. One solution is to transplant cells capable of differentiating into new blood vessels into the scaffolds to accelerate the creation of a vascularized scaffold. Because endothelial cells are the key cells involved in blood vessel formation, the present study was designed to investigate the development of a biomaterial surface that supports endothelial cell attachment and proliferation. The subsequent effects of the material surface modifications on the differentiation and proliferation of human bone marrow-derived fibroblasts (HBMFs) when grown in co-culture with a human bone marrow endothelial cell line (HBMEC-60) were studied. Endothelialization studies showed that the gelatin-coated and hydroxyapatite-coated substrates were superior for HBMEC-60 attachment and proliferation to hydrolyzed-only or untreated polycaprolactone substrates. Co-culture studies showed that the presence of the HBMEC-60 specifically enhanced HBMF cell proliferation and differentiation and that this effect was not observed with co-culture with skin fibroblasts. It is concluded that the co-culture of endothelial cells with HBMFs could be a promising culture system for bone tissue- engineering applications.